2011
DOI: 10.1021/ie1025002
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Structure, Interaction, and Properties of a Guanidinium-Based Ionic Liquid and Its Mixture with CO2

Abstract: Recently, the guanidinium-based ionic liquid N,N,N 0 ,N 0 ,N 00 -pentamethyl-N 00 -propylguanidinium tetrafluoroborate ([ppg][BF 4 ]) was found to be able to effectively absorb CO 2 (Amitesh, M. ChemSusChem 2009, 2, 628). In this work, molecular dynamics (MD) simulations and ab initio calculations were performed to investigate the microscopic structure, interactions, and properties of pure ionic liquid [ppg] [BF 4 ] and mixtures of [ppg][BF 4 ] (1) and CO 2 (2) at x 2 = 0, 0.1, 0.3, 0.5, 0.6. CÀH 3 3 3 F hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Another mechanism proposed to explain CO2 solubility in ILs is the presence of a free volume that can accommodate CO2 molecules. There is, however, no agreement on the location of this free volume as two theories have been proposed: (i) on the one hand, it is thought that the free volume is near the alkyl chain of the cation and (ii) on the other hand, some studies showed that the free volume could be located in the space between the cation and anion (Babarao et al, 2011;Zhang et al, 2011;Lei et al, 2014). Despite the uncertainty, the free volume is considered to play a significant role in CO2 solubility.…”
Section: Conventional Ionic Liquidsmentioning
confidence: 99%
“…Another mechanism proposed to explain CO2 solubility in ILs is the presence of a free volume that can accommodate CO2 molecules. There is, however, no agreement on the location of this free volume as two theories have been proposed: (i) on the one hand, it is thought that the free volume is near the alkyl chain of the cation and (ii) on the other hand, some studies showed that the free volume could be located in the space between the cation and anion (Babarao et al, 2011;Zhang et al, 2011;Lei et al, 2014). Despite the uncertainty, the free volume is considered to play a significant role in CO2 solubility.…”
Section: Conventional Ionic Liquidsmentioning
confidence: 99%
“…Fluorination of the cation or anion, ,, along with the introduction of ether and carbonyl groups in the cation, has also yielded increased physical solubility of CO 2 . Regarding anions, the following trend has been observed for the solubility of CO 2 in ionic liquids for a given cation: nitrate [NO 3 ] − < thiocyanate [SCN] − < methylsulfate [MeSO 4 ] − < tetraborofluorate [BF 4 ] − < trifluoromethanesulfonate [OTF] − < trifluoroacetate [TFA] − < [PF 6 ] − < bis­(trifluoromethanesulfonyl)­imide [NTf 2 ] − < perfluoroheptaneacetate [C 7 F 15 COO] − < tris­(pentafluoroethyl)­trifluorophosphate [eFAP] − < tris­(pentafluorobutyl)­trifluorophosphate [bFAP] − . An alternative theory for the high solubility of CO 2 in ionic liquids was proposed based on the results obtained from molecular dynamics (MD) and quantum mechanical calculations. These studies aimed to explain the gas solubility in terms of the existence of free volume in the ionic liquidsthe void space between ions. Typically, fluorinated ionic liquids are characterized by weaker cation–anion interactions and possess high molar volumes and free volume, both favorable for CO 2 solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CO 2 solubility has been explained in terms of molar volume or free volume of ILs with the help of molecular dynamic simulation, quantum, or simple calculations. The theory of free volume believes loosely held or weak ionic interactions create a space that is favorable for CO 2 solubility. , …”
Section: Introductionmentioning
confidence: 99%